2014
DOI: 10.1179/1973947814y.0000000180
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of integrons in clinical isolates of betalactamase-producingEscherichia coliandKlebsiella pneumoniaein Iran

Abstract: Integrons are considered to play a significant role in the evolution and spread of antibiotic resistance genes. A total of 349 clinical isolates of Escherichia coli and Klebsiella pneumoniae were investigated for molecular characterization of integrons and betalactamases. Antimicrobial susceptibility testing was also performed as the Clinical and Laboratory Standards Institute (CLSI) guidelines. The frequency of extended spectrum betalactamases (ESBL) or metallo-betalactamases (MBL)-producing isolates, patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
12
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 23 publications
8
12
2
Order By: Relevance
“…Sequencing analysis of the cassette arrays revealed a predominance of the dfrA17 and dfrA17-aadA5 arrays in this population. This finding agrees with those of previous studies reporting a strong association between class 1 integrons and the dfrA and aadA cassettes [15,33]. Indeed, the dfrA17 and aadA5 cassettes were formerly found in a class 1 integron of an E. coli isolated in 1998 from the urinary tract of an Australian patient [34].…”
Section: Molecular Characterization Of Gene Cassettessupporting
confidence: 83%
See 1 more Smart Citation
“…Sequencing analysis of the cassette arrays revealed a predominance of the dfrA17 and dfrA17-aadA5 arrays in this population. This finding agrees with those of previous studies reporting a strong association between class 1 integrons and the dfrA and aadA cassettes [15,33]. Indeed, the dfrA17 and aadA5 cassettes were formerly found in a class 1 integron of an E. coli isolated in 1998 from the urinary tract of an Australian patient [34].…”
Section: Molecular Characterization Of Gene Cassettessupporting
confidence: 83%
“…More than 130 gene cassettes encoding resistance to all classes of antibiotics and more than 60 gene cassettes of unknown function have been described in mobile integrons [13]. In Enterobacteriaceae, most gene cassettes associated with class 1 integrons encode resistance to streptomycin (aadA) and trimethoprim (dfrA) [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the class 1 integron containing the aadA1 gene was similar to that found in gram-negative bacteria [33]. Therefore, the transfer of resistance genes that may occur between ram-positive and gram-negative organisms could lead to the construction of diverse resistance to the usual antibiotics [34].…”
Section: Discussionmentioning
confidence: 52%
“…in 2015 in Zanjan, Iran, metallo-b-lactamase producing K. pneumoniae strains carried bla IMP and bla VIM were found in 100% and 41·6%, respectively. [21]…”
Section: Discussionmentioning
confidence: 99%